Sources and Detection of Dark Matter and Dark Energy in the Universe Proceedings of the 10th UCLA Symposium on Sources and Detection of Dark Matter and Dark Energy in the Universe, February 22-24, 2012, Marina del Rey, California - Cline, David (Springer Proceedings in Physics,, 2013)
These proceedings provide the latest results on dark matter and dark energy research. The UCLA Department of Physics and Astronomy hosted its tenth Dark Matter and Dark Energy conference in Marina del Rey and brought together all the leaders in the field. The symposium provided a scientific forum for the latest discussions in the field.  Topics covered at the symposium:  •Status of measurements of the equation of state of dark energy and new experiments •The search for missing energy events at the LHC and implications for dark matter search •Theoretical calculations on all forms of dark matter (SUSY, axions, sterile neutrinos, etc.) •Status of the indirect search for dark matter •Status of the direct search for dark matter in detectors around the world •The low-mass wimp search region •The next generation of very large dark matter detectors •New underground laboratories for dark matter search  .